2014
DOI: 10.1002/app.40429
|View full text |Cite
|
Sign up to set email alerts
|

Jamming rheology of model cementitious suspensions composed of comb‐polymer stabilized magnesium oxide particles

Abstract: The colloidal microstructure of concentrated suspensions containing anionic comb-polymer-stabilized magnesium oxide (MgO) particles in water was analyzed by shear rheometry for indications of changes in particle microstructure based on particle size and comb-polymer usage. As the suspensions were sheared at different rates, jamming in the sheared MgO suspensions was observed as shear stress overshoots. The shear-induced evolution of the suspension's microstructure was strongly related to the perceived interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…This suggests that these larger molecular weight comb polymers could have a greater steric stabilization effect due to their larger size. The magnitude of the molecular weight discovered here is consistent with reports from other research teams that found molecular weights around 20 000 g/mol of a similar concrete superplasticizer . It has been found in a study by Laarz and Bergstrom on stabilizing Si 3 N 4 at lower solids loading (20 vol%) that PMAA‐PEO grafted comb polymers effective as dispersants had molecular weights ranging from 37 200 to 43 200 g/mol …”
Section: Resultssupporting
confidence: 90%
“…This suggests that these larger molecular weight comb polymers could have a greater steric stabilization effect due to their larger size. The magnitude of the molecular weight discovered here is consistent with reports from other research teams that found molecular weights around 20 000 g/mol of a similar concrete superplasticizer . It has been found in a study by Laarz and Bergstrom on stabilizing Si 3 N 4 at lower solids loading (20 vol%) that PMAA‐PEO grafted comb polymers effective as dispersants had molecular weights ranging from 37 200 to 43 200 g/mol …”
Section: Resultssupporting
confidence: 90%
“…For example, the 30% free PEG suspension had an effective polymer concentration of 5.4 mg/mL surrounding the particles compared to the 18 mg/mL concentration of adsorbed PAA‐PEO comb‐polymer. In a previous study, it was found through ultraviolet–vis spectroscopy that less than 5% of the PAA‐PEO chains do not adsorb to particles …”
Section: Methodsmentioning
confidence: 99%
“…MgO particles were obtained from Martin Marietta Magnesia Specialties (MagChem P98 pulverized, Martin Marietta Magnesia, Baltimore, MD). Previous characterization of the MgO particles revealed the average particle size to be ∼4 µm with a range of sizes between 0.5 and 40 µm . ADVA 190 (Grace Construction, Cambridge, MA), a commercial water‐reducing PCE used in Portland cements, was applied as an additive for MgO suspensions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations